Current treatment practice of Guillain-Barré syndrome - Verboon, Christine; Doets, Alex Y.; Galassi, Giuliana; Davidson, Amy; Waheed, Waqar; Péréon, Yann; Shahrizaila, Nortina; Kusunoki, Susumu; Lehmann, Helmar C.; Harbo, Thomas; Monges, Soledad; Van den Bergh, Peter; et al. (American Academy of Neurology, 2019)
ObjectiveTo define the current treatment practice of Guillain-Barré syndrome (GBS).MethodsThe study was based on prospective observational data from the first 1,300 patients included in the International GBS Outcome Study. We described the treatment practice of GBS in general, and for (1) severe forms (unable to walk independently), (2) no recovery after initial treatment, (3) treatment-related fluctuations, (4) mild forms (able to walk independently), and (5) variant forms including Miller Fisher syndrome, taking patient characteristics and hospital type into account.ResultsWe excluded 88 (7%) patients because of missing data, protocol violation, or alternative diagnosis. Patients from Bangladesh (n = 189, 15%) were described separately because 83% were not treated. IV immunoglobulin (IVIg), plasma exchange (PE), or other immunotherapy was provided in 941 (92%) of the remaining 1,023 patients, including patients with severe GBS (724/743, 97%), mild GBS (126/168, 75%), Miller Fisher syndrome (53/70, 76%), and other variants (33/40, 83%). Of 235 (32%) patients who did not improve after their initial treatment, 82 (35%) received a second immune modulatory treatment. A treatment-related fluctuation was observed in 53 (5%) of 1,023 patients, of whom 36 (68%) were re-treated with IVIg or PE.ConclusionsIn current practice, patients with mild and variant forms of GBS, or with treatment-related fluctuations and treatment failures, are frequently treated, even in absence of trial data to support this choice. The variability in treatment practice can be explained in part by the lack of evidence and guidelines for effective treatment in these situations. © American Academy of Neurology.